Hyphenated GC-MS Determination of Volatile Constituents in Lilium - Wang, Xiaojing; Yu, Yueming; Guo, Sufen (Asian Journal of Chemistry, 2014)
Volatile components of lilium were extracted by water steam distillation and analyzed by using gas chromatography-mass spectrometry (GC-MS). A total of 72 volatile oil components were identified and the relative content of each component was determined by area normalization. Among 72 volatile oil components, 48 compounds identified amount to 77.28 % of the total amount of volatile oil. The major compounds were found to be 1-dodecene (8.04 %), 1-docosene (7.35 %), 1-hexadecanol (5 %), ethanol, 2-(9-octadecenyloxy)-, (Z)- (4.22%), n-hexadecanoic acid (3.27 %), benzofuran, 4,7-dimethyl- (3.26%) and hexadecane-1,2-diol (3.09 %).